Atenção, consciência e prática pedagógica: um estudo de suas interconexões - Cunha, Lúcia de Fátima da (2014)
This thesis entitled, Attention, Consciousness and Practice of Teaching: A Study of its Interconnects, argues about a relationship between development of attention and consciousness and its connection to the pedagogical practice developed in a public elementary school in Natal city, Rio Grande do Norte state. The research school is located in the south of the city. School activities are developed according with the political pedagogical project. The group investigated was 25 students aged between 8-12 years of the fourth grade. The students of the research are residents of Ponta Negra village, Pirangi and Neópolis districts. The research was effected by three teachers however, the purpose of this thesis was to investigate the relationship between the development of attention and awareness and the pedagogical practice of one of the teachers who participated in the research, and more specifically understand the psychic procedures involved in the development of attention and awareness; enabling conditions for the realization of an educational action that enables the development in terms of focused attention and states of consciousness of students, analyzing their interrelations. Therefore, it was used as methodology the collaborative research by providing elements for research as strategy of formation and development, the coproduction of knowledge, and the change of educational practice through reflective processes effected through the collaboration and critical reflection among participants. For empirical construction, it was used the following procedural elements: meeting, planning, diagnosis of attention and awareness, reflective period studies, collaborative observation and reflection sessions with the participant teachers and the students. The diagnosis of attention was effected through a game and its elaboration was based on the study proposed by Luria (1991). The purpose of the game was to apprehend the stage where students were in relation of a development attention. Concerning the diagnosis of consciousness, it was taken as reference studies by Burlatski (1987), Pinto (1960a, 1960b), Rubinstien (1973), Leontiev (1978) and others studies discussing this topic. As a method of analysis, it was resorted to the dialectical historical materialism, the ability to identify, analyze and explain those contradictions generated in the process. In the analysis procedures were prepared some categories as well as, were used categories by other authors with the purpose of understanding the critical reflective process collaborative evidencing the formation of concepts and pedagogical practice of the participants, and the analysis of a practical pedagogical of a teacher and her relationships with the development of the psychic process and functions of students, in other words, attention and awareness. Regarding the reflective process were used the categories: technical reflection, critical reflection and practical reflection (LIBERALI, 2008). Concerning the analysis of the concepts were used the categories: description, characterization, definition and conceptualization (FERREIRA, 2003). And for critical collaboration were the categories: critical collaboration, uncritical, technique and practice. In pedagogical practice, were used categories: repetitive practice teaching, heterogeneous and reflexive critical (SOUZA, 2010). During the collaborative observation was evident predominance of heterogeneous practice, because the main participant teacher searches for immediate solution to the situations problem, as well as reflection moments, is the technical arrangement, practice, critical, as well as concern in interacting with students, the qualitative changes, deep knowledge, renewal and transformation of the teaching activity. In this process, the collaborative reflection proved to be an effective strategy for developing awareness of students, because through reflection sessions, the students were able to understand that learning is a building process and that it necessary to be careful for their development